A collision free MAC protocol for energy saving in wireless ad hoc networks - G. Boggia; P. Camarda; M. Castellano; O. Fiume; L.A. Grieco; S. Mascolo (International Workshop on Wireless Ad-Hoc Networks, 2004., 2004)
Wireless ad hoc networks represent a powerful tool for enabling wireless networking where temporary network connectivity is needed. However, a wide deployment of wireless ad hoc networks relies on system architectures that provide energetic optimization. This paper describes a preliminary proposal of a collision free MAC protocol able to minimize energy consumption. The algorithm has been developed starting from the theory of balanced incomplete block design (BIBD). A simple analytical model has been proposed for evaluating the system performance (channel efficiency, energy saving, etc.), as a function of system parameters. The results show that the proposed architecture is able to provide, for an appropriate choice of system parameters, high channel efficiency and energy saving.
Keywords: Media Access Protocol; Wireless application protocol; Intelligent networks; Ad hoc networks; Mobile ad hoc networks; Synchronization; Wireless sensor networks; Power control; Interference; Propagation losses